2010
DOI: 10.1186/1477-7827-8-129
|View full text |Cite
|
Sign up to set email alerts
|

First trimester screening for trisomy 21 in gestational week 8-10 by ADAM12-S as a maternal serum marker

Abstract: BackgroundA disintegrin and metalloprotease 12 (ADAM12-S) has previously been reported to be significantly reduced in maternal serum from women with fetal aneuploidy early in the first trimester and to significantly improve the quality of risk assessment for fetal trisomy 21 in prenatal screening. The aim of this study was to determine whether ADAM12-S is a useful serum marker for fetal trisomy 21 using the mixture model.MethodIn this case control study ADAM12-S was measured by KRYPTOR ADAM12-S immunoassay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Several studies have described a positive correlation between the ADAM12‐s and PAPP‐A levels in the first trimester . In this study, we also found a strong positive correlation between MoM levels of PAPP‐A and ADAM12‐s in spontaneous pregnancies, which supports the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have described a positive correlation between the ADAM12‐s and PAPP‐A levels in the first trimester . In this study, we also found a strong positive correlation between MoM levels of PAPP‐A and ADAM12‐s in spontaneous pregnancies, which supports the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Some pathophysiologic conditions of pregnancy such as hypertensive disorders and aneuploidy may impact biomarker interpretation. (33-35) In addition, some markers, such as progesterone, may have altered expression in a pregnancy resulting from assisted reproduction. Our study demonstrated that prediction was independent of gestational age; however, it is possible that having data from one additional point of care, such as additional serum data from another time point (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A case control study of patients with EP and viable IUPs demonstrated that a level≤48.49ml/mL was 97% sensitivity and 37% specific for EP, suggesting promising utility as a marker of extra-uterine location. However, ADAM-12 has also been explored as a marker of aneuploidy, and as such, its performance amidst a cohort including abnormal IUPs must be considered (44, 45). Others have attempted to validate ADAM-12 and found that it did not discriminate EP from all other outcomes when including treated persisted PULs, spontaneously resolving PULs, and probable EPs (AUC 0.65, p>0.05) but when restricting the analysis to well defined PUL outcomes, it had slightly better diagnostic potential (AUC 0.66, p<0.05) (46).…”
Section: Markers Of Trophoblast Functionmentioning
confidence: 99%
“…Alternatively, including gestational age independent markers like certain microRNAs may be helpful (52). Second, one must consider the impact of other pathophysiologic processes of pregnancy such as hypertensive disorders and aneuploidy and how these may impact biomarker interpretation (24, 32, 44, 45, 120). In addition, some markers, such as progesterone, may have altered expression in a pregnancy resulting from assisted reproduction.…”
Section: Biomarker Discovery and Future Directionsmentioning
confidence: 99%